Continuous-Flow Processing of Gaseous Ammonia Using a Teflon AF-2400 Tube-in-Tube Reactor: Synthesis of Thioureas and In-Line Titrations - Browne, Duncan L.; O’Brien, Matthew; Koos, Peter; Cranwell, Philippa B.; Polyzos, Anastasios; Ley, Steven V. (Synlett, 2012)
A simple tube-in-tube reactor based on the gas-permeable membrane Teflon AF-2400 was used in the continuous flow reaction of gaseous ammonia with isothiocyanates and one isocyanate. A colourimetric in-line titration technique is also reported as a simple method to quantify the amount of ammonia taken up by the solvent in the system.
Keywords: gas-liquid flow chemistry; tube-in-tube; Teflon AF-2400; ammonia; in-line colourimetric titration